Regulation of Alternative Splicing by Signal Transduction Pathways: Lessons from Studying Variant RAC1b in Colon Cancer - Gonçalves, Vânia (2018)
Introduction: Alternative pre-mRNA splicing contributes significantly to both post-transcriptional regulation of gene expression and proteome diversity. While hereditary genomic mutations cause aberrant splicing in individual genes, somatic diseases such as cancer are characterized by more wide-spread changes in splicing patterns. These patterns can be affected by the presence of mutant splicing factors, epigenetic chromatin modulation, or in response to cellular signaling. Here we use the paradigmatic splice variant RAC1b to explore how signaling pathways are involved in the deregulation of alternative splicing in cell representing serrated colorectal tumors with mutations in the BRAF gene. Materials and Methods: HT29 colorectal cells harbor one mutant BRAF-V600E allele and overexpress RAC1b. Cells were transfected with shRNA vectors directed against target candidate protein kinase transcripts and their effects on RAC1b levels analyzed 24 h later by Western Blot and qRT-PCR. Treatment of cells with kinase inhibitors or anti-inflammatory drugs was performed 24 h prior to cell lysis. Results and Discussion: The presence of protein kinase BRAF-V600E was insufficient to change alternative splicing of RAC1b. Therefore, 20 candidate splicing-regulatory protein kinase genes were depleted by RNAi in HT29 cells and two kinases, SRPK1 and GSK3β, were found required to sustain RAC1b splicing levels. Both kinases were shown to act upon the phosphorylation level of splicing factor SRSF1, known to bind a spliceenhancing element in the alternative exon included in RAC1b. Reduced SRSF1 phosphorylation led to its reduced nuclear translocation and a concomitant reduction in RAC1b alternative splicing. GSK3β was further found to be a target of the anti-inflammatory drug ibuprofen. Mechanistic studies in HT29 cells revealed that ibuprofen but not aspirin, promoted a specific reduction in RAC1b splicing through an inhibitory phosphorylation of GSK3β. The reduction in RAC1b could be rescued when SRPK1 or SRSF1 were overexpressed in ibuprofen-treated cells, revealing the existence of a splicing-regulatory pathway. Together, our results indicate that alternative splicing in cancer cells can be deregulated through signal transduction pathways, e.g. in response to inflammatory stimuli. The data also identify a specific action of ibuprofen on alternative splicing of RAC1b and suggest it may be beneficial in treating patients with the subtype of BRAF-mutated serrated CRC.